Method for recovering copper in lead anode slime

The copper in the lead anode mud was recovered through the two-stage oxygen pressure leaching process, which solved the recycling problem caused by excessive copper content in the anode mud, and achieved efficient copper recycling and environmentally friendly process flow.

CN119710267APending Publication Date: 2025-03-28深圳市中金岭南有色金属股份有限公司韶关冶炼厂
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411560733.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, when recovering copper in lead anode mud, the copper content in the anode mud is too high, resulting in excessive viscosity of the melting slag during subsequent gold and silver recovery, affecting the settlement of metal silver. The acids and oxidants used in the copper decopper process will cause environmental protection problems, and it is difficult to meet the standards for wastewater treatment.

Method used

Using a two-stage oxygen pressure leaching process, firstly, the lead anode sludge is mixed with the first silica fluoric acid leaching solution for oxygen pressure leaching, separate the leaching solution and the leaching solution, and copper is recovered; then, the leaching residue is mixed with the second silica fluoric acid leaching solution for second oxygen pressure leaching, and copper is further recovered.

Benefits of technology

Through the two-stage oxygen pressure leaching process, the copper content in the anode mud can be effectively reduced, the copper leaching rate can be improved, energy loss and impurity introduction, production efficiency can be improved, and the recycling of fluorosiliic acid can be achieved, reducing environmental protection risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710267A_ABST
    Figure CN119710267A_ABST
Patent Text Reader

Abstract

The invention discloses a method for recovering copper in lead anode slime, which comprises the following steps: S1, mixing the lead anode slime with a first silicofluoride acid leaching solution, carrying out first-stage oxygen pressure leaching, separating to obtain a first-stage leaching solution and first-stage leaching residues, and recovering copper from the first-stage leaching solution; and S2, the first-stage leaching residues and second silicofluoride acid leaching liquid are mixed, second-stage oxygen pressure leaching is conducted, and second-stage leaching liquid and second-stage leaching residues are obtained through separation. According to the method for leaching and recovering the copper, the characteristic that the dissolved oxygen content in the solution is increased along with the increase of the pressure is utilized, the oxygen partial pressure in a reaction system is increased, the purpose of enhancing the oxidation effect is achieved, introduction of impurities in other oxidizing agents can be avoided, and the environmental protection problems of energy loss, volume expansion, slag amount increase and the like are solved; and the hydrofluoric acid leaching liquid is combined, so that the leaching efficiency and the leaching selectivity of the copper can be improved, the leaching rate of the copper after two-stage oxygen pressure leaching is 95% or above, and the content of the copper in secondary leaching residues is reduced to 0.5% or below.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nonferrous metal smelting, and in particular to a method for recovering copper from lead anode mud. Background Art

[0002] The electrolytic refining process of lead in industry mostly adopts the Paetz process, using an electrolytic system composed of silicic acid and lead silicic acid. During the production process, the copper content in the lead anode mud can reach 5-10%, which has a certain recovery value. The anode mud is composed of elements and compounds that are insoluble or difficult to dissolve in the electrolyte, mainly containing copper, lead, antimony, bismuth, tin, silver, arsenic, gold and other elements, and is an important raw material for recovering rare and precious metals such as gold and silver. Excessive copper content in the anode mud will have an adverse effect on the subsequent gold and silver refining process. When oxidizing and removing impurities in the silver separation furnace, the presence of a large amount of high-melting-point copper oxide slag will cause the viscosity of the molten slag to be too high and affect the precipitation of metallic silver, resulting in a high content of gold and silver in the silver separation furnace slag. Therefore, reducing the copper content in the anode mud is of great significance to improving the direct recovery rate of gold and silver.

[0003] The copper removal process of lead anode mud usually adopts the wet method. The leaching process requires the use of acid and oxidant, and most of them use sulfuric acid leaching. The anode mud after copper removal will contain a certain amount of sulfate. When the gold and silver are recovered by the subsequent pyrometallurgical method, it will face environmental problems caused by the absorption of low-concentration sulfur dioxide flue gas. In addition, iron powder is usually used to replace the copper in the leaching solution. The liquid after replacement enters the wastewater treatment. Because it contains a certain amount of fluorosilicic acid and organic additives brought in from the anode mud, such as sodium lignin sulfonate and bone glue, it is extremely difficult to meet the discharge standards by treating the wastewater alone. Therefore, it is particularly important to develop an anode mud copper removal technology with high recovery efficiency, no impurities introduced, and can be integrated with the original conventional process. Summary of the invention

[0004] In order to overcome the problems existing in the prior art, the object of the present invention is to provide a method for recovering copper from lead anode mud.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A first aspect of the present invention provides a method for recovering copper from lead anode mud, comprising the following steps:

[0007] S1, mixing the lead anode mud with the first silicic acid fluoride leaching solution, performing a first-stage oxygen pressure leaching, separating to obtain a first-stage leaching solution and a first-stage leaching residue, and recovering copper from the first-stage leaching solution;

[0008] S2, mixing the first leaching residue with the second silicofluoric acid leaching solution, performing two-stage oxygen pressure leaching, and separating to obtain the second leaching solution and the second leaching residue; the silicofluoric acid concentration of the second silicofluoric acid leaching solution is greater than the silicofluoric acid concentration of the first silicofluoric acid leaching solution.

[0009] Preferably, the first fluorinated silicic acid leaching solution and the second fluorinated silicic acid leaching solution are both aqueous solutions of fluorinated silicic acid.

[0010] Preferably, the concentration of silicic acid in the first silicic acid leaching solution is 40-70 g / L.

[0011] Preferably, the concentration of silicic acid in the second silicic acid leaching solution is 60-90 g / L.

[0012] More preferably, the concentration of silicic acid in the first silicic acid leaching solution is 60-70 g / L.

[0013] More preferably, the concentration of silicic acid in the second silicic acid leaching solution is 70-90 g / L.

[0014] Preferably, the oxygen partial pressure of the first stage oxygen pressure leaching is 0.2-0.7 MPa.

[0015] More preferably, the oxygen partial pressure of the first stage oxygen pressure leaching is 0.2-0.4 MPa.

[0016] Preferably, the oxygen partial pressure of the second-stage oxygen pressure leaching is 0.2-0.7 MPa.

[0017] More preferably, the oxygen partial pressure of the second-stage oxygen pressure leaching is 0.2-0.4 MPa.

[0018] Preferably, the solid-liquid ratio of the lead anode mud to the first fluorinated silicic acid leaching solution is 1kg:3-5L.

[0019] Preferably, the oxygen pressure leaching period lasts for 4 to 20 hours.

[0020] More preferably, the oxygen pressure leaching period is 4 to 8 hours.

[0021] Preferably, the second stage oxygen pressure leaching time is 4 to 20 hours.

[0022] More preferably, the oxygen pressure leaching period lasts for 5 to 9 hours.

[0023] Preferably, the second-stage leaching solution is circulated to the first-stage oxygen pressure leaching for secondary recovery.

[0024] The second-stage leaching solution contains a large amount of fluorosilicic acid and can be circulated to the first-stage oxygen pressure leaching to be used as the first silicic acid fluoride leaching solution.

[0025] Preferably, the leaching temperature of the first stage oxygen pressure leaching and the second stage oxygen pressure leaching are both 15-40°C.

[0026] Preferably, the first stage oxygen pressure leaching and the second stage oxygen pressure leaching are both carried out in an oxygen pressure reactor.

[0027] Preferably, electrolytic deposition is used to recover copper from the first-stage leaching solution to obtain copper and post-electrolytic deposition solution.

[0028] More preferably, the electrolytic anode of the electrolytic deposition is a graphite electrode or stainless steel, and the electrolytic cathode is stainless steel.

[0029] Further preferably, the post-electrolysis solution, the first-stage leaching residue and the second silicic acid fluoride leaching solution are mixed to carry out second-stage oxygen pressure leaching.

[0030] Electrolytic deposition of a fluorosilicic acid system is used to recover copper from a first leaching solution, and the recovered solution, i.e., the solution after electrolytic deposition, can be used as a second silicic acid fluoride leaching solution.

[0031] More preferably, the current density of the electrolytic deposition is 500 to 1500 A / m 2 .

[0032] Combined with high current density electrowinning to recover copper powder, the copper recovery rate in the same batch of materials is higher, the copper leaching rate in the anode mud is maintained above 96%, and the anode mud containing only 0.5% copper is obtained, which has positive significance for improving the equipment processing capacity and reducing the subsequent gold and silver recovery costs.

[0033] Preferably, the method further comprises subjecting the second-stage leaching slag to pyrometallurgical treatment to extract gold and silver.

[0034] The beneficial effects of the present invention are:

[0035] (1) The present invention provides a method for recovering copper from lead anode mud. The method utilizes the characteristic that the amount of dissolved oxygen in a solution increases with the increase of pressure to increase the oxygen partial pressure in a reaction system, thereby achieving the purpose of enhancing the oxidation effect. The method can avoid the introduction of impurities from other oxidants and reduce environmental problems such as energy loss, volume expansion, and increased slag. The method also uses pressurized oxygen leaching to quickly leach copper from anode mud, thereby improving production efficiency. The method uses high current density electrolysis to obtain copper powder. The fluorosilicic acid used can be recycled. After two-stage oxygen pressure leaching, the copper leaching rate is above 96%, and the copper content in the second leaching slag is reduced to below 0.5%. The reaction time is greatly reduced, and the leaching process can be completed in a total of 13 hours. The copper content in the first leaching slag is 86%.

[0036] (2) Compared with the normal pressure environment, the interaction between molecules in the oxygen pressure leaching system of the present invention is increased, the collision frequency is improved, the oxidation reaction efficiency can be effectively improved, and the hazard of hydrogen fluoride waste gas generated by the decomposition of silicofluoric acid is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Flow chart for recovering copper from lead anode mud. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.

[0039] Example 1

[0040] This embodiment provides a method for recovering copper from lead anode mud. Figure 1 The flow chart for recovering copper from lead anode mud is as follows:

[0041] (1) According to the liquid-solid ratio of 5:1, 1 kg of lead anode mud and 5 L of the first silicofluoric acid leaching solution (a solution composed of silicofluoric acid and water, with silicofluoric acid of 65 g / L) were added to the autoclave, and a pipeline was connected to introduce oxygen. Under room temperature, the oxygen partial pressure was kept constant at 0.3 MPa, and the reaction was stirred for 6 hours; filter pressing was performed to obtain a leachate and a leaching residue;

[0042] (2) Place a section of the leaching solution in an electrolytic equipment, use a graphite electrode as the anode and 304 stainless steel as the cathode for electrolytic deposition, and keep the constant current density at 600-800 A / m 2 , react for 4 to 6 hours, filter, and obtain sponge copper powder and electrodeposition liquid;

[0043] (3) The first-stage leaching residue and 5 L of the second silicofluoric acid leaching solution (a solution composed of silicofluoric acid and water, with a silicofluoric acid content of 80 g / L) were added to a pressure autoclave, connected with a pipeline, and oxygen was introduced. Under room temperature conditions, the oxygen partial pressure was kept constant at 0.3 MPa, and the reaction was stirred for 7 hours; the second-stage leaching solution and the second-stage leaching residue were obtained by filter pressing.

[0044] After the above process, the copper content in the first-stage leaching solution is 22.03g / L, the first leaching rate of copper is 80%, the copper in the second-stage leaching residue is only 0.48%, and the total leaching rate of copper is 96.81% (referring to the copper leaching rate of 1Kg raw material after the second-stage oxygen pressure leaching). After the electrolytic process, the copper content in the obtained post-electrolytic solution is 0.57g / L, and the copper content in the sponge copper powder is 86%.

[0045] Example 2

[0046] The difference between Example 2 and Example 1 is that the first silicofluoric acid leaching solution used in Example 2 is the second-stage leaching solution of Example 1, and the second silicofluoric acid leaching solution used in Example 2 is the post-electrolytic copper removal solution of Example 1, and the rest is the same as Example 1.

[0047] After the above process, the copper content in the first-stage leaching solution is 33.42 g / L, the first leaching rate of copper is 78%, the copper in the second-stage leaching residue is only 0.51%, and the total leaching rate of copper is 96.55%. After the electrolytic process, an electrolytic solution containing 0.98 g / L copper and a sponge copper powder with a grade of 81% are obtained.

[0048] Comparative Example 1

[0049] This comparative example provides a method for recovering copper from lead anode mud, and the specific steps are as follows:

[0050] (1) According to the liquid-solid ratio of 5:1, 1 kg of lead anode mud and 5 L of the first silicic acid leaching solution (a solution composed of silicic acid and water, with silicic acid content of 65 g / L) were added to the reaction barrel, a pipeline was connected, oxygen was introduced, and the reaction was stirred for 6 hours under room temperature and normal pressure conditions; filter pressing was performed to obtain a leachate and a leaching residue;

[0051] (2) Place a section of the leaching solution in an electrolytic equipment, use a graphite electrode as the anode and 304 stainless steel as the cathode for electrolytic deposition, and keep the constant current density at 600-800 A / m 2 , react for 4 to 6 hours, filter, and obtain sponge copper powder and electrodeposition liquid;

[0052] (3) Add the first-stage leaching residue and 5 L of the second silicofluoric acid leaching solution (a solution composed of silicofluoric acid and water, with a silicofluoric acid content of 80 g / L) into a reaction barrel, connect a pipeline, introduce oxygen, and stir the reaction for 7 h at room temperature and normal pressure; filter press to obtain the second-stage leaching solution and the second-stage leaching residue.

[0053] After the above process, the copper content in the second-stage leaching residue is 5.98%, and the total copper leaching rate is 55.67%.

[0054] Comparative Example 2

[0055] This comparative example provides a method for recovering copper from lead anode mud, and the specific steps are as follows:

[0056] (1) According to the liquid-solid ratio of 5:1, 1 kg of lead anode mud, 5 L of the first silicofluoric acid leaching solution (a solution composed of silicofluoric acid and water, with silicofluoric acid of 65 g / L) and 500 mL of hydrogen peroxide were added to the reaction barrel, a pipeline was connected, oxygen was introduced, and the reaction was stirred for 20 hours at room temperature and normal pressure; filter pressing was performed to obtain a leachate and a leach residue;

[0057] (2) Place a section of the leaching solution in an electrolytic equipment, use a graphite electrode as the anode and 304 stainless steel as the cathode for electrolytic deposition, and keep the constant current density at 600-800 A / m 2 , react for 4 to 6 hours, filter, and obtain sponge copper powder and electrodeposition liquid;

[0058] (3) The first-stage leaching residue, 5 L of the second silicofluoric acid leaching solution (a solution composed of silicofluoric acid and water, with silicofluoric acid at 80 g / L) and 500 mL of hydrogen peroxide were added to a reaction barrel, connected with a pipeline, and oxygen was introduced. The reaction was stirred for 10 h at room temperature and normal pressure. The second-stage leaching solution and the second-stage leaching residue were obtained by filter pressing.

[0059] After the above process, the copper content in the first leaching solution is 14.57 g / L, the first leaching rate of copper is 56%, the copper content in the second leaching residue is 0.64%, and the total leaching rate of copper is 96.4%.

[0060] In summary, comparative examples 1 and 2 use a reaction barrel as a leaching device. Under the same reaction time, comparative example 1 is leached under normal pressure conditions, and the total leaching rate of copper is 55.67%. The oxidation effect is poor, the oxygen consumption is large, and the oxygen utilization rate is low. In comparative example 2, hydrogen peroxide is added to enhance the oxidation effect, and the total leaching rate of copper can reach 96%, but the first stage leaching rate of copper is only 56%, and a large amount of hydrogen peroxide needs to be added, so that the system temperature is increased, causing the decomposition of part of the fluorosilicic acid. Due to the expansion of the solution volume, the expanded solution needs to be discharged regularly, so that the leaching time becomes longer. Embodiments 1 and 2 use a pressure reactor as a leaching device, and use a pressurized oxygen leaching method. The reaction time is greatly reduced, and the leaching process can be completed in a total of 13h. The leaching rate of copper exceeds 96%, and the work efficiency is higher. The first stage of copper is 80%, and the copper powder is recovered by combining high current density electrowinning. The recovery rate of copper in the same batch of materials is higher, reducing the residual valuable substances in the system, without introducing other impurities, and more economical and environmentally friendly. In Example 2, the second-stage leaching solution and the post-electrolysis solution produced in the process are recycled, the fluorosilicic acid is completely reused, no waste liquid is discharged, and the direct recovery rate of copper can reach more than 95%.

[0061] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for recovering copper from lead anode mud, characterized in that: The steps include: S1, mixing the lead anode mud with the first silicic acid fluoride leaching solution, performing a first-stage oxygen pressure leaching, separating to obtain a first-stage leaching solution and a first-stage leaching residue, and recovering copper from the first-stage leaching solution; S2, mixing the first leaching residue with the second silicofluoric acid leaching solution, performing two-stage oxygen pressure leaching, and separating to obtain the second leaching solution and the second leaching residue; the silicofluoric acid concentration of the second silicofluoric acid leaching solution is greater than the silicofluoric acid concentration of the first silicofluoric acid leaching solution.

2. The method for recovering copper from lead anode mud according to claim 1, characterized in that: The first silicofluoric acid leachate and the second silicofluoric acid leachate are both aqueous solutions of silicofluoric acid; and / or, the concentration of silicofluoric acid in the first silicofluoric acid leachate is 40-70 g / L; and / or, the concentration of silicofluoric acid in the second silicofluoric acid leachate is 60-90 g / L.

3. The method for recovering copper from lead anode mud according to claim 1, characterized in that: The oxygen partial pressure of the first stage oxygen pressure leaching is 0.2-0.7 MPa; And / or, the oxygen partial pressure of the second-stage oxygen pressure leaching is 0.2-0.7 MPa.

4. The method for recovering copper from lead anode mud according to claim 1, characterized in that: The solid-to-liquid ratio of the lead anode mud to the first fluorinated silicic acid leaching solution is 1kg:(3-5)L.

5. The method for recovering copper from lead anode mud according to claim 1, characterized in that: The oxygen pressure leaching time is 4 to 20 hours; And / or, the time of the second stage oxygen pressure leaching is 4 to 20 hours.

6. The method for recovering copper from lead anode mud according to any one of claim 1, characterized in that: The second-stage leaching solution is circulated to the first-stage oxygen pressure leaching for secondary recovery.

7. The method for recovering copper from lead anode mud according to claim 1, characterized in that: The leaching temperatures of the first stage oxygen pressure leaching and the second stage oxygen pressure leaching are both 15-40°C.

8. The method for recovering copper from lead anode mud according to any one of claims 1 to 7, characterized in that: Electrolytic deposition is used to recover copper from a first-stage leaching solution to obtain copper and post-electrolytic solution.

9. The method for recovering copper from lead anode mud according to claim 8, characterized in that: The current density of the electrolytic deposition is 500-1500A / m 2 .

10. The method for recovering copper from lead anode mud according to any one of claims 1 to 7, characterized in that: The method also includes subjecting the second leaching residue to pyrometallurgical treatment to extract gold and silver.